Soil physiochemical properties and landscape patterns control trace metal contamination at the urban-rural interface in southern China. (July 2019) - Li, Cheng; Sun, Ge; Wu, Zhifeng; Zhong, Honglin; Wang, Rongping; Liu, Xiaonan; Guo, Zhixing; Cheng, Jiong
Abstract: This study examined the influences of three subsets of environmental factors (i.e. soil physicochemical properties including pH, organic matters and soil texture, landscape patterns, and parent materials) on the spatial variations and sources of soil trace metal contamination across an urban-rural environmental gradient in Guangzhou City, southern China. We collected 318 surface soil samples from forests, orchards, farmlands, and urban lawns using a random tessellation design for selecting sample sites. The geo-accumulation indices showed that 18%–88% of soil samples were contaminated: moderate to high contamination with Cd and Hg, low to moderate contamination with Cu, Pb, Zn and Ni, and low contamination with As and Cr. However, less than 13% of soil samples were considered to have exceeded the national standards causing environmental and human health concerns. The mean geo-accumulation indices increased in the order of forest, paddy field/orchard, vegetable, road/residential, and park/residential areas for As, Cd, Ni, Pb, Zn, closely following a land disturbance gradient. Spearman Correlation and Cluster Analyses showed that Pb-Cu-Zn had traffic-related origins, Cd-Hg were mainly influenced by fertilization or industrial emissions, and As-Cr-Ni had geogenic origins for agricultural soils. In contrast, the Ni, Hg and Cd contamination sources for urban soils included both anthropogenic and geogenic origins. The Stepwise Regression and Partial Redundancy Analyses showed that three subsets of environmental factors explained 43%–87% of variations of soil contamination for both agricultural and urban soils. We concluded that soil contamination was mainly controlled by soil physiochemical properties followed by landscape patterns. Soil absorption of aerial loads of trace metal pollutants dominated the soil contamination processes. Our findings implied that improving soil physiochemical properties and landscape designs can strengthen environmental buffering and carrying capacity, thus alleviating soil contamination and reducing non-point-source pollution in the study region. Graphical abstract: Image 1 Highlights: 17.9%–87.7% of soil samples were contaminated with trace metals. Less than 13% of soils causing threats to environmental and human health. Trace metals were prone to accumulate in areas with high anthropogenic disturbances. Soil contaminants were grouped into Cu-Pb-Zn, As-Ni, Cd-Hg, and Cr by origins. Soils with higher pH and organic matters, and heavier texture are more polluted. Abstract : Soil physiochemical properties and landscape patterns control soil contamination at the urban-rural interfaces in a populated region, south China.